Hubungan antara Pola Resistensi OAT Lini Pertama dan Gradasi Gambaran Foto Toraks Penderita TB Paru MDR: [First-Line Antituberculosis Drugs Resistance and Chest X-Ray Pattern of Multidrug-Resistant Tuberculosis Patient] - Pramanindyah Bekti Anjani; Soedarsono Soedarsono (Faculty of Medicine Universitas Airlangga, 2016)
Background: Tuberculosis (TB) is a disease which has long been known and is still a cause of death in the world. The emergece of the drug resistance in TB treatment, particularly Multi drug-Resistance Tuberculosis (MDR TB) become a significant public health problem in many countries. The diagnosis of MDR TB based on culture results. In some cases radiographic feature with severe abnormalities consideres as MDR TB. From this phenomenon, there is no research that connects the resistance pattern of first line ATD with chest x-ray feature in patients with MDR TB. Methods: The research design are analytical observational with cross-sectional study conducted in outpatient clinic of MDR TB in Dr. Soetomo hospital. Subjects were patients who are following a theraphy program in outpatient clinic of MDR TB in Dr. Soetomo hospital from 2012 to 2014 who meet the inclusion and exclusion criteria. A total of 65 patients. Result: the result of this study showed that of all patterns of resistance, most of the MDR TB patients were classified as having severe chest radiograph. 27 patients with RH resistance patterns, there were 14(51.9%) who had a chest radiograph are classified as severe. 5 patients with RHS resistance patterns, 2(60%) vwho had a chest radiograph are classified as severe. 13 patients RHES resistance patterns, 8(61.5%) who had a chest radiograph are classified as severe. 20 patients with RHE resistance patterns, 14(70%) who had a chest radiograph are classified as severe. Conclusion: There were no significant association between resistance pattern of first line ATD and chest x-ray feature in patient with MDR TB.